Respostas
respondido por:
1
Y=X^2-2X
X^2-2X-Y=0
A)1
B)-2
C)-1
Delta= b^2-4.a.c
Delta= -2^2-4.1.(-1)
Delta= 4-4
Delta=0
-b+ou-raiz quadrada delta/2.a
-(-2)+raiz de 0/2.1
2+0/2
2/2
1
-(-2)-raiz de 0/2.1
2-0/2
2/2
1
S{1,1}
X^2-2X-Y=0
A)1
B)-2
C)-1
Delta= b^2-4.a.c
Delta= -2^2-4.1.(-1)
Delta= 4-4
Delta=0
-b+ou-raiz quadrada delta/2.a
-(-2)+raiz de 0/2.1
2+0/2
2/2
1
-(-2)-raiz de 0/2.1
2-0/2
2/2
1
S{1,1}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás